Community Structure of Sporulating Fungi on Decaying Litters of Shorea spp. - ISRAWATI HARAHAP; GAYUH RAHAYU; IMAN HIDAYAT (Indonesian Society for microbiology, 2013)
The community structure of sporulating fungi on decaying branch and leaf litters of Shorea spp. were studied to reveal the common saprobic fungi. The study was mainly based on morphological observation. Twenty-nine species of the sporulating fungi were found on Shorea spp. litters at Situ Gede and Bubulak forest area, Bogor, West Java. The fungi included seven species of Ascomycetes (Annulohypoxylon purpureonitens, Diatrype chlorosarca, Didymosphaeria epidermidis, Lophiostoma sp., Lophodermium sp., Pemphidium sp., and Valsa sp.) and 22 species of anamorphic taxa that consisted of 12 Coelomycetes (Coniella musaiaensis, Coryneum betulinum, Hendersoniopsis thelebola, Lasiodiplodia theobromae, Lasmeniella guaranitica, Leptodothiorella sp., Massariothea themedae, Pestalotia guepinii, Pestalotiopsis sp., Pseudolachnea hispidula, Septoriella sp., and unidentified species of Coelomycetes) and 10 Hyphomycetes (Beltraniella portoricensis, Cryptophialoidea fasciculata, Hermatomyces spaerichus, Kiliophora ubiensis, Minimidochium setosum, Monodisma fragilis, Nodulisporium sp., Stilbella fimetaria, Virgatospora echinofibrosa, and unidentified Hyphomycetes). The most common taxa occuring on decaying leaf litter were B. portoricensis and Pemphidium sp., while those on decaying branch material were L. theobromae and C. fasciculata. The fungal community was subtrate specific. The community on decaying branch litter was more diverse than that on leaf litter. The C/N ratio of the substrate was closely related to the structure of the community.